La frontera no deja ver la montaña: invisibilización de la cordillera de Los Andes en la Norpatagonia chileno-argentina - Núñez, Andrés (Revista de Geografía Norte Grande, 2021)
This article concerns the relationship between border and mountain. At a geohistoric perspective we analyzed the process through which the Andes lost cultural presence as a political boundary overlap. This has led to the present, the mountains and the Andes in Chile has been dominated by a reading that homologous with the idea of barrier or "line". From this perspective, the Anes is interpreted as a physical space serves to separate the "ones" of "other". That has obscured or minimized the socio-cultural value to the Andes has had historically and which has at present. Analyze the case of the Chilean North Patagonia-Argentina to show the historical enclave she meant and planned, which was re-meaning from the presence of a legal border